2011
DOI: 10.1093/infdis/jir039
|View full text |Cite
|
Sign up to set email alerts
|

Norovirus GII-4 Causes a More Severe Gastroenteritis Than Other Noroviruses in Young Children

Abstract: Norovirus (NoV) GII-4 has emerged as the predominant NoV genotype in outbreaks of gastroenteritis worldwide. We determined clinical features of NoV GII-4 associated acute gastroenteritis (AGE) in comparison with AGE associated with other NoV types in infants during seasons 2001 and 2002. During the prospective follow-up period, 128 primary infections of AGE due to NoV were identified in 405 infants; of these, GII-4 was found in 40 cases (31%). NoV GII-4 was associated with longer duration of diarrhea and vomit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
41
0
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 70 publications
(55 citation statements)
references
References 14 publications
8
41
0
2
Order By: Relevance
“…Thus, the multitude of young virus-positive patients suggested the possibility of primary infection in this study. A recent report suggested that GII/4 caused more severe disease than other NoV genotypes in cases of acute gastroenteritis in young children associated with primary infection [19]. In this study, 88 of the 119 sequenced strains (73.9%) were GII/4 strains in children ≤2 years of age; therefore, it is necessary to provide appropriate care for severe symptoms.…”
Section: Figmentioning
confidence: 74%
“…Thus, the multitude of young virus-positive patients suggested the possibility of primary infection in this study. A recent report suggested that GII/4 caused more severe disease than other NoV genotypes in cases of acute gastroenteritis in young children associated with primary infection [19]. In this study, 88 of the 119 sequenced strains (73.9%) were GII/4 strains in children ≤2 years of age; therefore, it is necessary to provide appropriate care for severe symptoms.…”
Section: Figmentioning
confidence: 74%
“…GII.4 strains have been reported to cause more severe illness [20,27] and a higher viral load in infected persons than other strains [28], which may lead to more frequent disease transmission. A higher environmental stability has also been discussed [26].…”
Section: Discussionmentioning
confidence: 99%
“…[13][14][15][16][17] Previous reports have shown that NoV GII strains are more likely to induce vomiting and severe diarrhea among children; similar observations were made in the current study. 18,19 A recent review that examined NoV outbreaks across the world showed an increase in NoV diarrhea. 20 This could be caused by the rapidity by which NoV has evolved that leads to distinct strains emerging every 2-4 years or wider availability of diagnostic tools.…”
Section: Discussionmentioning
confidence: 99%